CROSS CULTURAL DIDACTICISM: MORAL LESSON IN KOREAN KONG JWI PAT JWI AND INDONESIAN BAWANG MERAH PUTIH - Nismara, Zahra Adinda; Yulianeta; Samsudin, Didin (UIN Alauddin Makassar, 2024)
This article aims to identify and compare educational values contained in Bawang Merah and Bawang Putih, folklore from Indonesia, and Kong Ji Pat Ji from Korea through literary comparison. The study uses the qualitative descriptive method. Indonesian folklore was obtained through the 100-folklore book, and the origin of Korean folklore was obtained through the classic Korean folktale collection book. These two folk stories are similar: a main character living in a family where one parent dies and has a half-sister. Another similarity is that of the daughter in the family. Altogether, however, the text of these two folklores is different. The differences are found in text structures such as characters, settings, and grooves—furthermore, conflicts encountered in two different folklore. In the story of Bawang Merah and Bawang Putih, the protagonist seeks her stepmother's clothes, while in the story of Kong Ji Pat Ji fills the hollow. These two folk tales can be used as educational tools for moral and ethical values for readers of different cultural backgrounds.